Sonority effects in the production of fricative + sonorant clusters in polish - Castellví, Joan; Szmidt, Dorota T. (Lingua Posnaniensis, 2014)
This paper presents the results of a phonetic study on the occurrence of transition elements in Polish fricative + nasal clusters. A n acoustic study was carried out using the CSL system, with simultaneous observation of the waveform, spectrograph, glottal waveform and glottal pulses. T he results reveal differences in glottal activity depending on place of articulation of the fricative and in its duration with respect to the extent of glottal vibration. Differences in the glottal activity pattern and the transition elements between the fricative and the nasal were also observed. In the fricative-nasal limit three phenomena were found: a voiceless interval, a voiced interval and the absence of any transition element. It was also observed that the occurrence and the characteristics of the transition interval depend on the place of articulation of the fricative